2006
DOI: 10.1007/s00432-006-0120-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of soluble interleukin-2 receptor in patients with non-small cell lung cancer treated with gefitinib

Abstract: Our finding indicated that lymphocytes were activated by gefitinib treatment. We think that sIL-2R elevation after gefitinib administration may be a factor positively effecting patients with NSCLC. It is deemed possible that the effect of gefitinib is induced not only by its blocking of the tyrosine kinase of epidermal growth factor receptor but also by antitumor immunity via its activation of T-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…In an experimental study, EGFR blockade was associated with an enhanced inflammatory response (4). An increase in soluble P-selectin, RANTES and soluble interleukin-2 receptor was observed after administration of gefitinib, suggesting that gefitinib may activate cell-mediated immunity (5). On the other hand, no changes in systemic concentrations of vascular endothelial growth factor or basic fibroblast growth factor were observed after gefitinib therapy (14).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In an experimental study, EGFR blockade was associated with an enhanced inflammatory response (4). An increase in soluble P-selectin, RANTES and soluble interleukin-2 receptor was observed after administration of gefitinib, suggesting that gefitinib may activate cell-mediated immunity (5). On the other hand, no changes in systemic concentrations of vascular endothelial growth factor or basic fibroblast growth factor were observed after gefitinib therapy (14).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, original encouraging data with this drug (1, 2) were not confirmed by subsequent studies, and the drug is currently no longer available in the United States and European Union (15). Gefitinib seems to be more effective in Asian populations, and immune activation induced by the treatment with this drug has been reported in Asian patients (5). An increase of neopterin production has been documented in cancer patients after systemic administration of different cytokines (9) or with the combination of paclitaxel and doxorubicin (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If platelet activation is related to the anticancer effect the use of aspirin would decrease the effect of the EGFR-TKI. However, our previous study with gefitinib suggested that the effects of aspirin through inhibition of platelet COX-1 reduced the adverse effects of gefitinib but not its anti-cancer effects [4][5][6].…”
Section: To the Editormentioning
confidence: 95%
“…Tumor occurrence and progression are closely associated with body cellular immunity function. Serum soluble interleukin-2 receptor (SIL-2R) is an important monitoring index which can reflect the body cellular immunity function (Kanazawa et al, 2006). Hepatocyte growth factor (HGF), a multifunctional cytokine, is the most important factor that can promote the liver regeneration.…”
Section: Clinical Significance Of Joint Detection Of Serum Vegf Sil-mentioning
confidence: 99%